Phenomenal gender : what transgender experience discloses - Janssen, Ephraim Das (Indiana University Press, 2017)
Just what is gender, and what can be expected of it when dealing with identity, justice, and equality? Ephraim Das Janssen uses a phenomenological approach to challenge and dismantle the way gender is currently understood. Janssen questions ideas that have formerly been taken for granted, as individuals did during the Civil Rights movement, the women's movement, and the LGBT rights movement. In so doing he recasts the moral debate about gender and grounds his analysis in observable aspects such as clothing and social roles and how these can imply transgression and questioning. Janssen shakes the very core of gender through a deep engagement with Being and the structures that confine our contemporary notions. -- Provided by publisher.